2011
DOI: 10.2147/opth.s22243
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy, and intraoperative characteristics of DisCoVisc and Healon ophthalmic viscosurgical devices for cataract surgery

Abstract: PurposeTo evaluate the safety and efficacy of DisCoVisc ophthalmic viscosurgical device (OVD, Alcon Laboratories, Inc) with respect to a comparator, Healon OVD (Advanced Medical Optics, Inc).Patients and methodsIn this prospective study, patients with cataracts were randomized to an OVD, and then received phacoemulsification and injection of an intraocular lens. After each surgery, unmasked investigators completed subjective questionnaires about OVD characteristics during each stage of the procedure. Masked te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Another recent study with intraindividual comparisons of 78 eyes from 39 patients found significantly lower mean ECL with viscous-dispersive use (1.0%) than with very low viscosity dispersive use (3.5%) at 6 months after phacoemulsification [45]. Despite these results, studies comparing mean ECL of patients who received viscous-dispersive OVDs versus those who received soft-shell technique (N ¼ 50 eyes, viscous-dispersive: 5%; N ¼ 50 eyes, soft-shell technique: 4.11%) and cohesive OVDs (N ¼ 123 eyes, viscous dispersive: 6.4%; N ¼ 116 eyes, cohesive: 8.8%) during phacoemulsification showed no significant difference in ECL between groups at 3 months follow-up [46,47]. Another more recently developed device combines a cohesive OVD and ancillary lidocaine.…”
Section: Ophthalmic Viscoelastic Devicesmentioning
confidence: 99%
“…Another recent study with intraindividual comparisons of 78 eyes from 39 patients found significantly lower mean ECL with viscous-dispersive use (1.0%) than with very low viscosity dispersive use (3.5%) at 6 months after phacoemulsification [45]. Despite these results, studies comparing mean ECL of patients who received viscous-dispersive OVDs versus those who received soft-shell technique (N ¼ 50 eyes, viscous-dispersive: 5%; N ¼ 50 eyes, soft-shell technique: 4.11%) and cohesive OVDs (N ¼ 123 eyes, viscous dispersive: 6.4%; N ¼ 116 eyes, cohesive: 8.8%) during phacoemulsification showed no significant difference in ECL between groups at 3 months follow-up [46,47]. Another more recently developed device combines a cohesive OVD and ancillary lidocaine.…”
Section: Ophthalmic Viscoelastic Devicesmentioning
confidence: 99%
“…Protection could be related to endothelium-coating properties of the OVDs. Modi et al 18 reported their two studies using animal eyes that a thin uniform layer of DisCoVisc OVD remained as a lining on the inner cornea after phacoemulsification and removal of OVD. It was suggested that this coating was indicative of the protective effects of the DisCoVisc OVD.…”
Section: Discussionmentioning
confidence: 99%
“…22 The constituents provide not only physical protection, but also chemical protection. 22 Medilon contains polyacrylamide 1.5%.…”
Section: Discussionmentioning
confidence: 99%
“…22 The constituents provide not only physical protection, but also chemical protection. 22 Medilon contains polyacrylamide 1.5%. Polyacrylamide is known as highly biocompatible and being used in the production of soft contact lenses and as viscoelastic agent in ophthalmic surgeries.…”
Section: Discussionmentioning
confidence: 99%